Pelatihan, Pendampingan dan Sertifikasi ISO 9001:2015 di UMKM XYZ, Mojokerto, Jawa Timur - Riski Ayu Anggreini; Diana Aqidatun Nisa; Nurul Widji T.; Ajeng Ananda Putri; Zelvia Dian Anggreini (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2022)
XYZ UMKM is a UMKM that is engaged in processed catfish, especially shredded meat, located in Mojokerto, East Java. UMKM production capacity has reached 20 kg/day however, given the large production capacity of these UMKM, ISO 9001:2015 standardization has not yet been implemented. ISO 9001:2015 is an international standard that implements a quality management system whose activities include quality assurance of an organization or business entity. The application of ISO 9001:2015 standardization is important in achieving quality standards for UMKM because it can guarantee quality, service, and provide customer satisfaction. Standardization of ISO 9001:2015 is a solution to the problems that faced by XYZ UMKM. The forms of activities that have been carried out are training on the application of IS0 9001:2015, assistance in making documents and recordings of ISO 9001:2015 standardization, audits and visits, and ISO 9001:2015 certification. The result of these activities is that XYZ UMKM have been certified to ISO 9001: 2015 and have understood and implemented ISO 9001: 2015 in the catfish shredded business. With the implementation of this standard, it supports a better performance quality management system, improving the quality and service quality of catfish shredded products.